Economic Contributions of the Florida Citrus Industry in 2015-16 - Christa D. Court; Alan Wade Hodges; Mohammad Rahmani; Thomas Spreen (EDIS, 2018)
This 2-page fact sheet written by Christa D. Court, Alan W. Hodges, Mohammad Rahmani, and Thomas H. Spreen and published by the UF/IFAS Food and Resource Economics Department describes the economic contributions of the citrus industry to the state of Florida in fiscal year 2015/16, updating previous studies for 2012/13 and 2014/15 and previous estimates for the economic impacts of citrus greening disease. edis.ifas.ufl.edu/fe1021